2017
DOI: 10.1124/dmd.117.075655
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Feeding Alters Expression of Hepatic Drug-Metabolizing Enzymes in Mice

Abstract: Medical conditions accompanying obesity often require drug therapy, but whether and how obesity alters the expression of drug-metabolizing enzymes and thus drug pharmacokinetics is poorly defined. Previous studies have shown that high-fat diet (HFD) feeding and subsequent obesity in mice lead to altered expression of transcriptional regulators for cytochrome P450 CYP2D6, including hepatocyte nuclear factor 4 (HNF4, a transcriptional activator of CYP2D6) and small heterodimer partner (SHP, a transcriptional rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…6B-C). Results in liver are consistent with previous reports (Fromenty, 2013) although discrepancies still exist regarding the regulation of Cyp3a11 expression in the liver of high-fat fed mice (Ning and Jeong, 2017). Intriguingly, expression levels of Cyp2b10, a CAR target gene (Aleksunes and Klaassen, 2012), was significantly down-regulated in jejunum and up-regulated in liver from HFHS-fed mice.…”
Section: Gene Expression Analysis Of Xenobiotic Receptorssupporting
confidence: 90%
“…6B-C). Results in liver are consistent with previous reports (Fromenty, 2013) although discrepancies still exist regarding the regulation of Cyp3a11 expression in the liver of high-fat fed mice (Ning and Jeong, 2017). Intriguingly, expression levels of Cyp2b10, a CAR target gene (Aleksunes and Klaassen, 2012), was significantly down-regulated in jejunum and up-regulated in liver from HFHS-fed mice.…”
Section: Gene Expression Analysis Of Xenobiotic Receptorssupporting
confidence: 90%
“…Although data showed so many DMPK members regulated by high fat diet, there are still some unsolved problems. For example, a research regarding high fat diet and drug metabolizing enzymes revealed that high fat diet regulates endogenous CYPs in a gene-specific manner [10]. Until now, hundreds of CYP isozymes have been identified, but the effect of High fat diet effect on CYPs has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The WD increased significantly the expression of the hepatic Cyp3a11, the murine homolog of human CYP3A4, one of the key enzymes involved in drug metabolism [75] and in bile acid detoxification [76,77]. A recent study also showed that diets rich in saturated fat increase murine Cyp3a11 levels [78,79]. The diet switch was able to prevent the increase of Cyp3a11 an important observation for the treatment of IBD, because many drugs applied in IBD are metabolized by CYP3A4 [80].…”
Section: Discussionmentioning
confidence: 97%